Perhitungan Invers Kinematik pada Jalan Robot Humanoid - Rahmawati, Annisa; Rizal, Yusmet (UNIVERSITAS NEGERI PADANG, 2024)
Inverse kinematics is a mathematical calculation for robot motion design. With the known value of the desired coordinate point, this calculation determines the angles needed to move each joint on the robot. One of the solutions to the inverse kinematic equation can use the geometric approach method. This method is used to obtain angles on each axis of robot motion so that the end-effector can reach the desired position. In this geometric method approach, the three-dimensional (3D) viewpoint is decomposed into a two-dimensional (2D) viewpoint to facilitate the analysis and calculation process. Humanoid robots have 4 phases to walk, namely Double Support Phase, Pre-swing Phase, Single Support Phase, and Post-Swing Phase. By implementing the inverse kinematic formula into the C++ programming language, the humanoid robot can walk by entering the x, y, and z coordinate values. The x coordinate value regulates the tilt of the robot, the y coordinate value regulates the back and forth movement of the robot's legs, and the z coordinate value regulates the height of the robot's legs.